2003
DOI: 10.1063/1.1559437
|View full text |Cite
|
Sign up to set email alerts
|

InGaAs/InAlAs avalanche photodiode with undepleted absorber

Abstract: We report an avalanche photodiode with an undepleted p-type InGaAs absorption region and a thin InAlAs multiplication layer. The motivation for utilizing an undepleted absorption layer, which is similar to that in the unitraveling carrier photodiode, is to reduce the dark current. A dark current below 1 nA at a gain of 10 and a gain–bandwidth product of 160 GHz are demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 14 publications
1
20
0
1
Order By: Relevance
“…The device reported in Ref. [11] with a 150-nm n − -multiplication layer and p-absorption layer showed similar performances to APD-2 with larger S M=10 and S M=20 . In brief, APD-2 showed optimized overall performances with low operating voltage, relative small gain slope and un-sacrificed gain factor.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The device reported in Ref. [11] with a 150-nm n − -multiplication layer and p-absorption layer showed similar performances to APD-2 with larger S M=10 and S M=20 . In brief, APD-2 showed optimized overall performances with low operating voltage, relative small gain slope and un-sacrificed gain factor.…”
Section: Resultsmentioning
confidence: 75%
“…Larger gains of M>20 are accompanied by large dark currents and excess noises. By comparing with other InAlAs/InGaAs SAM APDs reported in literatures with a uniform E (∼700 kV/cm at M∼10) in the avalanche region [11]- [14], it was found that the gain slope and the operating voltage at M=10 and 20 (as denoted by S M=10 , V M=10 , S M=20 and V M=20 , respectively) for APD-2 are clearly lower than that reported in APDs with thinner multiplication layers [12]- [14], whereas the measured maximum M is much higher. The gain slopes S M=10 and S M=20 are, however, larger than that reported in Refs.…”
Section: Resultsmentioning
confidence: 86%
“…Table 1 lists the k eff values of 1D APDs from different research groups [17][18][19][20] and 3D-APDs in this paper. From the comparison, we can discover that 3D structure can help to reduce the excess noise factor with comparatively thicker multiplication layer, which avoids high tunneling current.…”
Section: Resultsmentioning
confidence: 98%
“…We used the ionization coefficients for In Al As reported by Saleh et [26]. The symbols represent the measured data reported by Li et al. al.…”
Section: Gain-bandwidth Productmentioning
confidence: 99%
“…As a validation of the our model, we computed the GBP of a 150-nm InAlAs APD developed by Li et al [26]. We used the ionization coefficients for In Al As reported by Saleh et [26].…”
Section: Gain-bandwidth Productmentioning
confidence: 99%